Current Pharmacogenetic Perspective on Stevens-Johnson Syndrome and Toxic Epidermal Necrolysis - Cheng, Lin (Frontiers in Pharmacology, 2021)
Adverse drug reactions is a public health issue that draws widespread attention, especially for Stevens-Johnson syndrome (SJS) and toxic epidermal necrolysis (TEN) which have high mortality and lack of efficacious treatment. Though T-cell mediated HLA interacted immune response has been extensively studied, our understanding of the mechanism is far from satisfactory. This review summaries the environmental risk factors, such as infections (virus, bacterial and mycoplasma infection), as a trigger for SJS/TEN. The mutations or polymorphisms of drug metabolic enzymes, transporters, receptors, the immune system genes, and T-cell mediated apoptosis signaling pathways that contribute to the SJS/TEN are discussed and summarized. Future research on epigenetics, metabolites, mobilization of regulatory T cells and tolerogenic myeloid precursors are emerged to be promising. Ex vivo lymphocyte transformation test has been exploited to aid identifying the causative drugs. Critical questions on the pathogenesis of SJS/TEN underlying gene polymorphism and T cells’ cytotoxicity remain: why some of patients carry the risky genes tolerate the drug and do not develop SJS/TEN; what makes the skin and mucous membrane so special to be targeted, do they relate to skin/mucous expression of transporters; the common machinery underlying different HLA-B alleles associated with SJS/TEN, and common metabolites.